2014
DOI: 10.1111/bjd.12915
|View full text |Cite
|
Sign up to set email alerts
|

Which factors predict incident pressure ulcers in hospitalized patients? A prospective cohort study

Abstract: SummaryBackground The prevention of pressure ulcers (PU) is an important public health issue owing to their substantial clinical and economic burden. Objectives To investigate predictors of incident PU in hospitalized patients and the performance of the Braden Scale in intensive care units (ICU) and normal care units (NCU). Methods We conducted a prospective cohort study including all inpatients treated at the University Hospital Carl Gustav Carus Dresden, Germany, between 2007 and 2011. Documentation comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
5
15
0
2
Order By: Relevance
“…Secondary data analysis of general ICU, medical and surgical patients, found that the probability of developing a PI in ICU was 4Á3 times higher than ward patients (Lahmann et al 2011). Similarly, Petzold et al (2014) found that treatment in ICU increases the risk of PI fourfold; the risk is cumulative as length of stay increases (Boyle & Green 2001, Cox 2011. In one study of surgical ICU patients, the incidence of PI grade II-IV occurring at least 48 hours after admission was 20Á1% (Nijs et al 2009).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Secondary data analysis of general ICU, medical and surgical patients, found that the probability of developing a PI in ICU was 4Á3 times higher than ward patients (Lahmann et al 2011). Similarly, Petzold et al (2014) found that treatment in ICU increases the risk of PI fourfold; the risk is cumulative as length of stay increases (Boyle & Green 2001, Cox 2011. In one study of surgical ICU patients, the incidence of PI grade II-IV occurring at least 48 hours after admission was 20Á1% (Nijs et al 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, Petzold et al . () found that treatment in ICU increases the risk of PI fourfold; the risk is cumulative as length of stay increases (Boyle & Green , Cox ). In one study of surgical ICU patients, the incidence of PI grade II‐IV occurring at least 48 hours after admission was 20·1% (Nijs et al .…”
Section: Introductionmentioning
confidence: 99%
“…Univariate analysis helped to identify length of stay as one of the significant predictors for PI development. Risk for PI occurrence was higher in patients who stayed more than 30 days in the hospital [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Figure 1: Diagrammatic representation of a conceptual framework, newly developed had shown the relationship between the outcome variable and independent variables. Source: Supported by different literatures (5,8,10,16,(20)(21)(22)(23)25) . …”
Section: Introductionmentioning
confidence: 99%